Answer: x = 5 , y = -1
Step-by-step explanation:
Given:
x + y = 4 ................. equation 1
x - y = 6 .................. equation 2
Solving the simultaneous equation by elimination method;
From equation 1 make x the subject of the formula , that is
x = 4 -y ............ equation 3
substitute equation 3 into equation 2 , we have
4 - y - y = 6
4 - 2y = 6
Add 2y to both sides , we have
4 = 6 + 2y
subtract 6 from both sides , we have
4 - 6 = 2y
- 2 = 2y
divide both sides by 2
-2/2 = y
Therefore : y = -1
Substitute y = -1 into equation 3 , we have
x = 4 - (-1)
x = 4 + 1
x = 5